Impacts of work‐at‐home policies on systems engineers and the general population. Issue 4 (3rd March 2022) - Perez‐Pereda, Maria Jose; Babvey, Pouria; Ramirez‐Marquez, Jose; Pepe, Kara; Verma, Dinesh
Abstract: The COVID‐19 pandemic presented many challenges, one of them being the imposition of "work‐at‐home" policies in March 2020. The Systems Engineering Research Center (SERC) and the International Council on Systems Engineering (INCOSE) conducted two online surveys—one during the first months of the pandemic in 2020 and the second survey 1 year after, in March 2021—to understand the impact of these policies within the systems engineering community. The surveys' format consisted of multiple‐choice questions and open‐answer questions, which were analyzed using LDA for topic modeling. Data were also collected from social media during the same timeframes to compare the feelings and experiences of systems engineers with those of the general population.